The Ministry of Trade and Industry Decree No. 1535 of the Year 2017 On Imposing Final Anti-Dumping Duties on Imports of Steel Rebar Item (Coils, Rods and Bars) Originating or imported from China, Turkey and Ukraine = وزارة التجارة والصناعة قرار رقم 1535 لسنة 2017 بفرض رسوم نهائية لمكافحة الإغراق على الواردات من صنف حديد التسليح (أسياخ ولفائف وقضبان وعيدان) المصدرة من أو ذات منشأ الصين وتركيا وأوكرانيا - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic